Impact of oncogene rearrangement patterns on outcomes in patients with double‐hit non‐Hodgkin lymphoma. Issue 4 (13th November 2015) - Landsburg, Daniel J.; Petrich, Adam M.; Abramson, Jeremy S.; Sohani, Aliyah R.; Press, Oliver; Cassaday, Ryan; Chavez, Julio C.; Song, Kevin; Zelenetz, Andrew D.; Gandhi, Mitul; Shah, Namrata; Fenske, Timothy S.; et al.
Abstract : BACKGROUND: Double‐hit lymphomas (DHLs) are collectively defined as B‐cell non‐Hodgkin lymphomas harboring rearrangements of MYC as well as B‐cell lymphoma 2 ( BCL2 ) and/or B‐cell lymphoma 6 ( BCL6 ). To the authors' knowledge, the impact of specific oncogene rearrangements on outcomes of patients with DHL who are treated with immunochemotherapy has not been previously described. METHODS: The authors identified patients whose diagnostic tissue specimens underwent metaphase karyotyping or fluorescence in situ hybridization for MYC as well as both BCL2 and BCL6 rearrangements. Cohorts were defined by the presence (+) or absence (−) of rearrangements: MYC +/ BCL2 +/ BCL6 − (BCL2‐DHL), MYC +/ BCL2 −/ BCL6+ (BCL6‐DHL), and MYC +/ BCL2 +/ BCL6 + (triple‐hit lymphoma; THL). RESULTS: A total of 117 patients were included in the current analysis (76 BCL2‐DHL patients, 16 BCL6‐DHL patients, and 25 THL patients). Compared with patients with BCL2‐DHL, those with BCL6‐DHL were more likely to be classified as having a non‐germinal center cell of origin, presented with extranodal disease, and appeared to achieve higher rates of complete response despite receiving intensive induction therapy less frequently. However, patients with BCL6‐DHL experienced a shorter median overall survival if achieving an initial complete response compared with patients with BCL2‐DHL. Patients with THL experienced survival outcomes similar to those of patients with BCL2‐DHL. CONCLUSIONS: Recognition of the specific oncogene rearrangements may be of prognostic value and potentially guide future therapeutic strategies for patients with DHL. Cancer 2016;122:559–564. © 2015 American Cancer Society . Abstract : To the authors' knowledge, the current study is the first large comparative analysis of double‐hit lymphomas by patterns of oncogene rearrangement. Patterns of oncogene rearrangement may be predictive of outcome in patients with double‐hit lymphoma as well as response to targeted therapies.